Design of a portable paddy cleaning machine - Shayfull Zamree, Abd. Rahim; Mohd Fathullah, Ghazli@Ghazali; Mohd Azaman, Md Deros (2011)
International Conference on Design and Concurrent Engineering (iDECON 2010) organized by Universiti Teknikal Melaka, 20th - 21st September 2010 at Renaissance Hotel, Melaka, Malaysia.